Contribution of quality management practices for business innovation - Gomes, Mafalda Filipa Figueiredo (2017)
Quality used to be an important differentiation factor, however, nowadays, innovation is considered the key factor for firms to survive in the modern highly competitive global market. This shift may take firms to consider also a move from a quality goal to an innovation goal, as they may perceive that the two goals are competing rather than complementary. A literature review on the relationship between quality and innovation performance was conducted and, despite the literature not be able of providing one general and clear answer for the type of relationship between quality and innovation, most studies suggest that a relationship exists, and quality can have a positive impact regarding innovation performance, providing a positive platform for its arising. The empirical study conducted under this dissertation also demonstrates than firms mostly perceive the quality practices they use as beneficial to their innovative processes and performance.